2017
DOI: 10.1007/s11011-017-9969-4
|View full text |Cite
|
Sign up to set email alerts
|

Ras-like without CAAX 2 (RIT2): a susceptibility gene for autism spectrum disorder

Abstract: Ras-like without CAAX2 (RIT2) which encodes a GTP-binding protein has recently been reported as a new susceptibility gene for Autism Spectrum Disorders (ASD) in a genome-wide association study. Since the gene is suggested to be involved in the pathogenesis of different neurological diseases, we investigated the association of two single nucleotide polymorphisms (SNP) rs16976358 and rs4130047 of this gene with ASD in Iranian patients. A total of 1004 individuals, comprising 532 ASD cases and 472 healthy subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…The neuronal, Ras-like GTPase, Rit2 (aka: Rin, ras-like in neurons), is enriched in DANs [8] and is required for NGF-mediated MAP kinase activation in neuroendocrine cells [9,10]. Multiple genome-wide association studies (GWAS) identified Rit2 in several DA-related disorders, including PD [11], ASD [12], essential tremor, schizophrenia, and bipolar disorder [13][14][15]. We previously demonstrated that Rit2 binds directly to the presynaptic, cocaine-sensitive DAT, and that Rit2 activity is required for PKC-stimulated DAT endocytosis in cell lines [16].…”
Section: Introductionmentioning
confidence: 99%
“…The neuronal, Ras-like GTPase, Rit2 (aka: Rin, ras-like in neurons), is enriched in DANs [8] and is required for NGF-mediated MAP kinase activation in neuroendocrine cells [9,10]. Multiple genome-wide association studies (GWAS) identified Rit2 in several DA-related disorders, including PD [11], ASD [12], essential tremor, schizophrenia, and bipolar disorder [13][14][15]. We previously demonstrated that Rit2 binds directly to the presynaptic, cocaine-sensitive DAT, and that Rit2 activity is required for PKC-stimulated DAT endocytosis in cell lines [16].…”
Section: Introductionmentioning
confidence: 99%
“…Rit2 activity is required for NGFmediated p38 MAP kinase and ERK activation in neuroendocrine cells (Shi, Han, and Andres 2005;Uenaka et al 2018). Moreover, Rit2 gene expression is enriched specifically in DA neurons (Zhou et al 2011), and several recent GWAS studies identified Rit2 SNPs and long tandem repeat variants associated with multiple DArelated disorders, including Parkinson's disease, ASD, and schizophrenia (Glessner et al 2010;Pankratz et al 2012;Zhang et al 2015;Emamalizadeh et al 2017;Foo et al 2017;Hamedani et al 2017). However, despite its disease association, relatively little is known about endogenous DAergic Rit2 function.…”
Section: Introductionmentioning
confidence: 99%
“…Rit2 (AKA: Rin) is a neuronal small GTPase that lacks a CAAX domain, and associates with the plasma membrane in a phosphoinositide-dependent manner (28)(29)(30). Rit2 gene expression is highly enriched in DA neurons (31), and several recent GWAS studies identified Rit2 SNPs and long tandem repeat variants associated with multiple DA-related disorders, including PD, ASD, and schizophrenia (32)(33)(34)(35)(36)(37). However, despite its disease association, relatively little is known about endogenous DAergic Rit2 function.…”
mentioning
confidence: 99%
“…Rit2 (AKA: Rin) is a neuronal small GTPase that lacks a CAAX domain, and associates with the plasma membrane in a phosphoinositide-dependent manner (28)(29)(30). Rit2 gene expression is highly enriched in DA neurons (31), and several recent GWAS studies identified Rit2 SNPs and long tandem repeat variants associated with multiple DA-related disorders, including PD, ASD, and schizophrenia (32)(33)(34)(35)(36)(37). However, despite its disease association, relatively little is known about endogenous DAergic Rit2 function.…”
mentioning
confidence: 99%